THE IMPORTANCE OF SERUM IMMUNOGLOBULINS IN THE DIAGNOSIS OF LATENT TUBERCULOSIS INFECTION IN CHILDREN - Rustamova S.A., Muazzamov B.R. (Central Asian Journal of Medicine, 2025)
This article, based on medical research, is dedicated to studying diagnostic indicators crucial for the diagnosis and treatment of latent tuberculosis infection (LTBI) in children, as well as preventive measures aimed at preventing the development of clinical forms of tuberculosis among them. Latent tuberculosis infection is defined as a state of persistent immune response to stimulation by Mycobacterium tuberculosis (MTB) antigens without any clinical evidence of active tuberculosis. Our research objective was to improve the effectiveness of detecting LTBI among children using immunological methods. A total of 90 children were involved in the clinical and immunological examination. In all children involved in the study, indicators related to humoral immunity, specifically the main classes of serum immunoglobulins were determined using the immunoenzyment analysis method with test systems corresponding to each indicator. While IgM and IgG levels were significantly increased in children with tuberculosis by 2.35 and 1.33 times, respectively, compared to the parameters of healthy children (p<0.05 and p<0.001), the levels of IgA and IgE were within the parameters of the control group and did not differ significantly from them (p>0.05). This suggests stress in the humoral component of the immune system and activation of the immune system.